Metaeffector regulation of Legionella pneumophila translation inhibiting effectors - Joseph, Ashley Marie (Kansas State University, 2022)
Legionella pneumophila is a facultative, intracellular bacteria that naturally infects free living amoeba and is an accidental human pathogen. L. pneumophila possesses a Dot/Icm type IV secretion system that transfers over 330 effector proteins directly into its host cell. This large arsenal of effectors contributes to the ability of L. pneumophila to establish infection in both environmental and immune phagocytes. Effectors modulate host cell processes to acquire nutrients and generate a camouflaged replication compartment called the Legionella containing vacuole (LCV) which mimics the appearance of rough endoplasmic reticulum. Survival within the host cell relies on proper coordination and regulation of effector activity throughout the infection process. L. pneumophila encodes a subset of effector proteins, called metaeffectors, that regulate the activity of another effector or family of effectors. The metaeffector, MesI, is required for L. pneumophila intracellular replication in Acanthamoeba castellanii and bone marrow-derived macrophages in the context of its target effector, SidI. SidI is one of seven effectors known to inhibit host mRNA translation. We found that MesI suppresses both SidI translation inhibition and novel mannosyl hydrolase activity. It was additionally discovered that MesI binds SidI at two, non-overlapping regions on the N-and C- terminus and does not interfere with SidI binding to the eukaryotic elongation factor, eEF1A. Further investigation revealed that the deleterious phenotype associated with loss of mesI is due to SidI intrabacterial toxicity that can be replicated in vitro with overexpression of sidI uncoupled from mesI. Given the importance of MesI regulation of SidI to L. pneumophila survival, we investigated another toxic translation inhibiting effector, SidL, that interacts with a putative metaeffector, LegA11. In addition to translation inhibition, SidL binds to filamentous actin and inhibits actin polymerization in vitro, but the effects of LegA11 on these activities are unknown. We uncovered that LegA11 regulates both SidL translation inhibition and inhibition of actin polymerization, despite promoting binding to actin. Interestingly, we discovered that loss of legA11 provided a replication advantage during intracellular replication in murine Nlrc4-deficient macrophages, but not in Acanthamoeba castellanii, THP-1 cells or the mouse lung. This advantage was not attributed to improved establishment of the LCV or an increase in bacterial growth rate and the cause of the replication advantage is unknown. Here we highlight commonalities in metaeffector regulation of translation inhibiting effectors, while demonstrating the differential contributions of metaeffectors to L. pneumophila intracellular replication. This work provides valuable insight into the dynamic and intricate regulation of L. pneumophila effectors and contributes to the broader understanding of complex host-pathogen interactions exerted by intracellular pathogens.
Keywords: Legionella pneumophila; Effector; Metaeffector; Translation inhibition